Motivation of achievement and problem solving with linear functions at a university in Surco - Rostaing Ccapacca, Gean Pierre (2019)
The objective of this research study was to determine the relationship between the motivation of achievement and the resolution of problems with linear functions of the students of Foundations of Calculus for the afternoon course of the Faculty of Business at the Peruvian University of Applied Sciences, 2017. This study was developed within a quantitative approach, with a hypothetical deductive method and non-experimental design. The sample consisted of 76 students of Foundations of Calculus from the Faculty of Business of the aforementioned university. The results show that there is no direct and significant relationship between the motivation of achievement and the resolution of problems with linear functions of the students surveyed. This further showed that the competency to solve problems does not depend on motivation, but rather requires knowledge and skills that are put into practice.